A series of misfortunes of women in Sudha Murty's novel ‘Mahashweta’ - Dr. Hemlata (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
India's Sudha Murthy is a well-known name. She has authored numerous works about the human relationships between mothers and children. Women's issues with their husbands and in-laws are the primary subject of the book. She has received numerous distinguished honours. The themes of her books, Dollar Bahu, Mahashweta, and Gently Falls the Bakula, centre on the psychological struggles that married women face. Even though they are completely committed and involved, they endure a lot of terrible circumstances throughout their lives and are eventually compelled to leave their husband's home. Since no one can relate to their mental state or the awful life they lead because of her illness, they bravely resolve to leave their home in order to live independently and refrain from getting married again. The marriage proposal she got is never accepted. Sudha Murthy's "Mahashweta" is the best illustration of how to dispel common misconceptions about women and emphasize their contributions to society. The protagonist longs for identity in the oppressive patriarchal society, takes a new step, and begins the journey to freedom. In the end, this process leads to varied degrees of independence.